I'm trying to substitute one Differential equation into another differential equation.

eq1:=d*n(t)/dt = (rho(t)-beta)*n(t)/Lambda+lambda*C(t)+q

eq2:=diff(eq1, t)

resulting in -> eq2 := d*(diff(n(t), t))/dt = (diff(rho(t), t))*n(t)/Lambda+(rho(t)-beta)*(diff(n(t), t))/Lambda+lambda*(diff(C(t), t))

then I'm given that (diff(C(t), t)) is given by another equation:

eq3:=d*C(t)/dt = beta*n(t)/Lambda-lambda*C(t)

At this point I'm trying to substitute equation 3 into equation 2 for diff(C(t),t)

eq4 := subs(diff(C(t), t) = rhs(eq2), eq5)

however no matter what way's I try this I get an error:

Error, (in simpl/reloprod) invalid terms in product: (d*(diff(n(t), t))/dt = (diff(rho(t), t))*n(t)/Lambda+(rho(t)-beta)*(diff(n(t), t))/Lambda+lambda*(diff(C(t), t)))^-1

I then tried to map it but again i got an error specifically about the first parameter:

Error, invalid operator parameter name

eq5:=map((d/dt C(t))->beta/Lambda*n(t)-lambda*C(t),eq2)

I'm just wondering if what I am trying to do is even possible in Maple?

If anyone can help I would greatly appreciate it!